Understanding the Laws of Harvest: Black and Latino Male Collegians Enacting Critical Race Care as Youth Mentors. Issue 12 (December 2021) - Clark, Jelisa S.; Brooms, Derrick R.; Smith, Matthew; Franklin, William
Background/Context: In recent years, there has been a proliferation of student engagement programs intended to increase college access, retention, and graduation for Black and Latino males. Although supporting Black and Latino male students' educational opportunities and success efforts is an urgent need, few studies examine their collective leadership experiences—either on campus or in the community. These experiences are important in understanding how engagement and leadership are vital components for Black and Latino males' sense of self, community ties, and collective consciousness. Focus of Study: We investigate the collegiate experiences and engagement of 12 Black and Latino male students in the Brothers Empowering Collective Achievement (BECA; pseudonym), a male-centered program at a Hispanic-serving institution. We explored their leadership and mentoring experiences through the following research questions: (1) How do Black and Latino college men make sense of their engagement in a male-centered success program? (2) What factors influence Black and Latino males' decisions to serve in a leadership capacity as youth mentors? (3) What is the focus of Black and Latino males' leadership work as youth mentors? (4) What do Black and Latino males take away from their experiences as youth mentors? Intervention/Program/Practice: The BECA program is an academic and social engagement program that was developed in an effort to increase graduation and retention of Latino and Black men. BECA provides professional workshops, one-on-one and small group mentoring, community service opportunities, and various other social activities. In addition, strategic partnerships with local schools allow college students to mentor middle and high school students. Research Design: This qualitative study is based on focus group interviews with 12 Black and Latino male students at a Hispanic-serving institution related to their leadership experiences as youth mentors for local middle school and high school students. Findings/Results: Our findings show that students were nested in, benefited from, and enacted critical race care—expressed as holistic care for youth, which considers their racialized identities and experiences as well as various facets of their lives in supporting their needs and development—through their BECA engagement. According to the men's narratives, BECA provided a unique opportunity to bring Black and Latino males together to pursue individual and collective goals. In addition, serving in leadership roles as youth mentors within the local community enhanced the men's sense of self and allowed them to contribute to community education and youth development. Conclusion/Recommendations: This study speaks to the value and benefits Latino and Black men accrue from critical race care. Specifically, being engaged and embedded in a community in which they pursue collective educational and personal goals enhances engagement, leadership, and relationships for Black and Latino college students.